The Nexus of Religion, Ethnicity, and Money: Understanding Political Violence Against Women in Eastern Indonesia - Kurniawati Hastuti Dewi; Fransiska Widyawati; Ade Latifa; Ari Purwanto Sarwo Prasojo; Nur Iman Subono (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2026)
The 2024 General Elections in Indonesia were marked by significant cases of Violence Against Women in Politics (VAWP), including in Eastern Indonesia. This study aims to present the Islamic Law and Christian Perspective as the dominant faiths in Eastern Indonesia, on women’s involvement in politics. It also explores how, in the context of the 2024 elections, religious identity, ethnicity, money, and non-indigenous sentiment have been weaponized to perpetuate VAWP in Eastern Indonesia. This is qualitative research, based on in-depth interviews with female politicians in Eastern Indonesia, particularly in East Nusa Tenggara and West Papua. This study reveals that both Islamic Law and Christian perspectives allow women to participate in politics in the region. However, female candidates in East Nusa Tenggara encountered psychological violence (where their religious affiliations and ethnic backgrounds were frequently weaponized against them) and economic violence (manifested through voters’ high demands for material inducements in exchange for electoral support). More interestingly, Muslim women candidates in predominantly Christian regions in West Papua were subjected to psychological violence linked to their religious identity and perceptions of being non-indigenous women. This study concludes that VAWP in Eastern Indonesia is highly complex, as the interplay of religious diversity, ethnic identities, money and issues concerning non-indigenous sentiment intensifies its manifestations. These dynamics leave women politicians particularly vulnerable, especially in the absence of sufficient protective mechanisms. This study suggests the need for comprehensive legislation to address violence against women in politics (VAWP) at both national and local levels.